Analisis Semiotika dalam Novel Lebih Senyap dari Bisikan Karya Andina Dwifatma - Restu, Neri Nurtiana; Shomary, Sudirman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
Literary works appear as a form of reflection of people's lives and the feelings expressed by interacting with life. The language used by the author has a certain meaning. Language in the form of signs is interesting to study semiotically. Semiotics is the science that studies signs which have three aspects, namely the icon, index and symbol aspects. The novel Silent Than a Whisper by Andina Dwifatma tells the story of Amara and the baron having a child. The problems of this research are (1) What is the semiotic aspect of the icon contained in the Novel More Silent Than a Whisper by Andina Dwifatma?, (2) What is the semiotic aspect of the index contained in the Novel More Silent Than a Whisper by Andina Dwifatma?, (3) What is the symbolic aspect contained in the novel Silent Than a Whisper by Andina Dwifatma?. The aim of this research is to describe, analyze and conclude data on icons, indexes and symbols in the Novel Silent Than a Whisper by Andina Dwifatma. This research uses a qualitative approach. The research method uses descriptive methods. The data collection technique used is the hermeneutic technique. The data analysis technique uses content study. The data validity technique uses triangulation techniques. The theory used is Pradopo's theory (2017). The results of this research are that the icon for the entire Novel Silent Than a Whisper by Andina Dwifatma is 37 data, the index for the entire Novel Silent Than a Whisper by Andina Dwifatma is 14 data. There are 33 symbols for the entire novel Silent Than a Whisper by Andina Dwifatma. The results of this research are that the author found the existence of icons, indexes and symbols. The most dominant aspect in this novel is symbols. The reason this aspect is more dominant is because symbols are related to culture.